Understanding the implementation and efficacy of a home-based strength and balance fall prevention intervention in people aged 50 years or over with vision impairment: a process evaluation protocol - Lisa Dillon; Lindy Clemson; Kristy Coxon; Lisa Keay (BMC, 2018)
Abstract Background A nested process evaluation, within a randomised controlled trial, will explore relationships between program outcomes and quality of intervention implementation of the Lifestyle-Integrated Functional Exercise Program in older people with vision impairment. The Lifestyle-Integrated Functional Exercise Program is a home-based strength and balance program that has been shown to reduce falls in high risk populations. A pilot study showed positive trends in improvements in physical function in older people with vision impairment after participation in the program. The program will be delivered by Orientation and Mobility Specialists, who are experienced in working with people with vision impairment. Methods The process evaluation has a mixed methods design. This includes quantitative (fidelity checklist score, number of completed sessions, survey data and a habit formation scale), as well as qualitative (open responses from program staff and semi-structured interviews with study participants) data. Process evaluation measures include program adherence (fidelity), complete delivery (dose delivered), participant receipt (dose received) and participant enactment. Using the Behaviour Change Wheel, a logic model was built to explain the intended inputs, outputs, outcomes and relationships to the behaviour change techniques in the Lifestyle-Integrated Functional Exercise Program in older people with vision impairment. Discussion The findings of the process evaluation will inform the provision of fall prevention programs in older people with vision impairment by Orientation and Mobility Specialists. To date, there are no proven falls prevention programs which aim to improve physical function and reduce falls in older people with vision impairment. This process evaluation will contribute new knowledge about the implementation of a strength and balance program in this population. Trial registration ACTRN12616001186448. Registered 29 August 2016.